It's a Different World: A Dialog on the Attention-Based View in a Post-Chandlerian World. (April 2023) - Ocasio, William; Yakis-Douglas, Basak; Boynton, Dylan; Laamanen, Tomi; Rerup, Claus; Vaara, Eero; Whittington, Richard
In this Dialog, seven scholars consider the theoretical implications and research opportunities a changing environment presents for the Attention-Based View (ABV). With its roots in the 1950s Carnegie School, ABV is expanding and evolving in ways that accommodate the changes in the corporate context characterized by distributed, porous structures of organizational networks such as ecosystems and platforms. The authors emphasize a shift toward a more dynamic orientation of this research, one that addresses the challenges of sustaining coherent attention and sensemaking, a shift from quantity to quality of attention, and how corporate communications ranging from formalized strategy presentations to less formal social media communications can spin attention in ways that lead to intended as well as unintended outcomes. Emerging organizational trends open up radically different perspectives on attention: today's superstar firms draw new kinds of attention and many new business models are based upon the attraction and selling of customer attention.